PROBLEM ASPECTS OF ENSURING ENVIRONMENTALLY SAFE NATURE USE DURING THE POST-WAR RECONSTRUCTION PERIOD OF UKRAINE - Anisimov Vadym Mykolayovych (Research Retrieval and Academic Letters, 2024)
The study of the socio-economic aspect of ecologically safe nature management during the post-war recovery period of Ukraine is presented and provides grounds for stating the existence of serious, not fully realized by both scientists and practitioners, problems regarding the provision of a socially oriented component of mechanisms for implementing the system of effective nature management in the practice of post-war economic reconstruction.